Forest cover controls the nitrogen and carbon stable isotopes of rivers - Machado-Silva, Fausto; Neres-Lima, Vinicius; Oliveira, Andrea Franco; Moulton, Timothy Peter (The Science of the total environment, 2022)
Deforestation affects the ecological integrity of rivers and streams, threatening biodiversity and ecosystem services worldwide. However, few studies have strictly analyzed the effect of the functional responses of tropical streams to changes in forest cover since deforested basins are usually also influenced by confounding anthropogenic inputs. Here we address tropical streams and test whether the stable isotopic ratios of nitrogen (N, δ15N) and carbon (C, δ13C) and the ratio of C:N of ecosystem components vary along a forest cover gradient. We also assess the ecological integrity of streams by in situ measurements using physical features commonly used in stream quality assessments. The results showed that the δ15N of most aquatic components, δ13C of particulate matter and omnivorous fish, and C:N of particulate matter and algae vary significantly with forest cover, indicating the role of terrestrial vegetation in regulating stream biogeochemistry. The dual stable isotope analysis satisfactorily indicated the changes in terrestrial-aquatic connections regarding both N and C cycles, thus showing the role of algae and particulate matter in influencing stream fauna through food web transfers. Our results support the use of stable isotopes to monitor watershed deforestation and highlight the need for reassessment of the effects of anthropogenic inputs on δ15N increase in globally distributed inland waters since the loss of forest is a significant cause in itself. The influence of deforestation on the stable isotopic ratio (δ15N and δ13C, ‰) of stream ecological components. Left shows a forested basin and right a deforested basin where streams have less canopy shading. Values indicate the average and one stadard deviation of δ15N (black) and δ13C (purple) for fish, aquatic insects, filamentous algae, periphyton, and fine particulate matter. [Display omitted] •δ15N and δ13C of stream components are determined in a deforestation gradient.•δ15N and δ13C of stream biota and particulate matter increase with forest loss.•δ15N and δ13C can be used to monitor and diagnose deforestation in watersheds.